Building a dam and irrigation system to help farmers in Isabela, the Philippines, adapt to climate change, 2011–18 - Choi, Sooyoung (KDI School of Public Policy and Management, Global Delivery Initiative, 2020)
Farmers in Isabela, a province in the Philippines, have long suffered from natural disasters such as flooding and drought, and climate change has made farming even more difficult. In the 1990s and 2000s, droughts lasted longer, typhoons became more frequent, and the timing of seasons varied unexpectedly, making it difficult for farmers to predict rainfall. Most farmers in the region depended solely on rainfall to cultivate crops, which meant they could harvest only once a year. As a consequence, farms had low productivity, and many farmers struggled to get by. To reduce the impact of extreme weather, the government of the Philippines in 2011 launched the Pasa Dam project to build a dam, construct irrigation infrastructure, and improve management of the watershed, the land area that soaks up rainfall and channels it and underlying groundwater into rivers and lakes. Ultimately, the government aimed to increase agricultural production through a consistent supply of irrigated water. The project team faced several challenges in their efforts to build the dam, including typhoons, bankruptcy of the main construction contractor, and deforestation of the watershed area. To deal with the challenges, the team had to maintain strong relations with the local community and frequently adapt the construction plans. The dam and irrigation infrastructure were finally completed in 2018. In 2019, it was still too early to evaluate the project’s impact, but signs were encouraging. There was no flood or drought damage in the area in 2018 and 2019, and the dam was able to withstand two typhoons. Moreover, crop yield in the 2019 dry season was twice as high as it had been previously, and some farmers had begun harvesting twice per year.
Keywords: Agriculture; Water; Environment; Natural Resources